GLOSA DO WYROKU SĄDU OKRĘGOWEGO W SZCZECINIE Z DNIA 26 MARCA 2010 ROKU (SYGN. I C 28/101) - Osuchowska, Marta (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The verdict has been voted on in a dispute concerning the placing of religious symbols in public places. The subject of this gloss is to draw attention to the reasons of the court concerning the religious symbolism in the public space, with a particular focus on buildings of public authority. The court noted that the interpretation of the concept of “impartiality” in the case of Polish constitutional order does not mean indifference. The existing dispute between meaning of “impartiality” and “neutrality” is not adequate resolved. This results in the adoption of the open nature of the concept of neutrality in the Polish legal system. When placing religious symbols in the municipal office building, there is no legal basis for it directly allow. There is also no prohibitions that prevent such developments. This is due to the application of the right to manifest religious beliefs of people working in the indicated building. In turn, the symbolism of the cross in a public space can not violate the dignity, or can not restrict or cause of social exclusion of a mature person holding a worldview. Therefore, religious symbols hanging out at the premises of public authorities, in itself, does not affect the freedom of religion and conscience of individual citizens. The court in Szczecin held that the provisions of art. 25.2 of the Polish Constitution does not prohibit the placing of religious symbols in public spaces, in particular in the offices.